O Casal do Clérigo (Cascais) entre o século V e o século X - Cardoso, Guilherme; Batalha, Luísa (Estudos Arqueológicos de Oeiras, 2022)
The reduction of the trading between Olisipo and the other cities of the Roman Empire forced a readjustment of the population of the ager Olisiponensis to an economy of subsistence. Located in the countryside along the old Roman road from Oeiras to Sintra, the villa of Clérigo is one of the regional examples of the profound social changes operated between the V century, an alternation verifiable through the traces of the cultural material left by the residents of that period.